Effectiveness of Using Polymer Bumpers to Mitigate Earthquake-Induced Pounding between Buildings of Unequal Heights - Jian He; Yu Jiang; Qichao Xue; Chunwei Zhang; Jingcai Zhang (Advances in Civil Engineering)
Collisions often happen between adjacent buildings without a sufficient gap under seismic loadings. Installing polymer bumpers may decrease the pounding forces between colliding buildings. This paper focuses on the analysis of suppressing pounding effects by using of polymer bumpers. In order to investigate pounding mitigation effectiveness in the condition with and without bumpers, different types of pounding force models are utilized to simulate and calculate frame vibration responses under seismic loads. Firstly, time-history results for pounding force, displacements, and shearing forces in selected floors are calculated in the condition with and without polymer bumpers. Secondly, differences between viscoelastic and elastic pounding force models are compared and discussed. And finally, parametric studies are carried out to investigate influences of different pounding parameters. The results show that polymer bumpers can reduce maximum values of pounding force but increase pounding times. And viscoelasticity of bumper materials has a certain range of influences on pounding force responses. Choosing improper material types and pounding parameters may lead to opposite effects.